Seasonal regrowth capacity of an Amelichloa clandestina (Hack.) Arriaga & Barkworth grassland in northeastern Mexico (Agro Productividad, 2026)
Objective:To evaluate yield components and seasonal biomass accumulation of Mexican needlegrass (Amelichloa clandestina) at different days after regrowth (DAR) under the environmental conditions of northeastern Mexico. Design/Methodology/Approach: A completely randomized block design with three replicates was employed, considering days after regrowth within each season as the main study factor. The variables evaluated included dry matter yield (DMY), morphological components (MC), plant height (PH), and light interception (LI). Results: Maximum DMY was recorded between 75 and 90 DAR during autumn, reaching 546.1 kg DM ha⁻¹ (p ≤ 0.05), with a significant leaf contribution of 382.2 kg DM ha⁻¹. The greatest plant height (47.3 cm) was also observed in autumn at 90 DAR (p ≤ 0.05), accompanied by 42% light interception. A strong positive correlation was identified between DMY and plant height (R² = 0.83). Limitations/Implications: This study was conducted under the specific climatic conditions of northeastern Coahuila, Mexico. Therefore, the applicability of the results may vary under different environmental contexts. Findings/Conclusions: Amelichloa clandestina exhibited its greatest regrowth potential in autumn, as evidenced by increases in dry matter yield and plant height, along with a positive correlation with days after regrowth, outperforming the other seasons evaluated.